La noción de marco y sistema de referencia para la enseñanza de la relatividad del movimiento en la física clásica - Gallo Aconcha, Oscar Fernando (Revista Científica, 2011)
The introduction of the teaching of modern physics and particular the relativity of motion in the secondary education has become in the last decade a concern for teaching researchers and physics teachers. This proposal aims show the importance of the concepts and framework frame of reference in classical relativity and how influence and teaching of relativity of motion. In many cases the understanding of some concepts has not been achieved in the best manner, causing failures when analyzing phenomena and deal whit the validity of theoretical propositions that account for the same, this is particularly true when teaching subjects related to relativity of motion. The work is limited to show how the notions of movement, inextricably linked to notions of context and reference latter are very far from a simple definition.